Peningkatan Kompetensi Menulis Karangan Eksposisi Dengan Pendekatan Kontekstual Siswa Kelas X UPT SMAN 14 Jeneponto - Syahriani Syahriani; Kasma F.Amin; Rahmat Rahmat (Journal on Education, 2023)
This study aims to (1) describe the process of applying a contextual approach in writing exposition essay competence in class X Merdeka C UPT SMAN 14 Jeneponto, and (2) describe the results of increasing learning competence in writing exposition essays with a contextual approach in class X Merdeka C UPT SMAN 14 Jeneponto. The data source is all students of class X Merdeka C totaling 31 students. Data collection techniques were carried out using student observation sheets and tests/assignments. The data analysis used in this study is qualitative and quantitative. This research was conducted for two cycles. The process of applying the contextual approach in learning to write exposition essays in cycle I students are in the inactive category and in cycle II they increase to become active. While the learning outcomes of writing exposition essays by applying a contextual approach in cycle I obtained an average value of 69 and increased in cycle II to 86. Based on the Minimum Completeness Criteria (KKM), which is 75, it can be concluded that students' competence in writing exposition essays using a contextual approach increased.